Arctic Frost? Understanding Inuit Ambiguity towards Idle No More - Hanrahan, Maura (Lapin yliopisto, 2016)
This chapter explores apparent Inuit ambiguity towards Idle No More. The Indigenous movement was founded in Canada in 2010 to protest the Conservative government’s attempts to erode Indigenous sovereignty and reduce federal environmental protection, including in the Arctic, through omnibus legislation. Inuit perspectives on the movement are complex and reflect Inuit culture, priorities, and pressing realities. publishedVersion